Determining the Nutritional Value and Quality Indicators of Meat-Containing Bread Made With Hemp Seeds Flour (Cannabis sativa L.) - Bozhko, Nataliia; Pasichnyi, Vasyl; Tyshchenko, Vasyl; Marynin, Andriy; Shubina, Yevgenia; Strashynskyi, Igor (My University, 2021)
Meat-containing bread with the use of hemp flour has been devised, with the subsequent assessment of its physical and chemical, sensory properties involving the study into the technological indicators of new products. Three experimental formulations for meat-containing bread were developed, which included semi-fat pork, poultry, mechanically deboned turkey, pumpkin pulp, and 8, 10, 12 % of hemp flour. A meat-containing bread from combined raw materials was adopted as control. All samples were evaluated taking into consideration their physical and chemical, technological, and sensory characteristics. It has been proven that the addition of hemp flour to the formulation improved the consumer value of products by increasing the content of protein, fat, and minerals. It was found that the protein content in the developed products was 18.03‒19.53 g/100 g, which is 3.21‒11.80 % higher than that of the analog. The fat content increased by 17.84–56.83 %, which also led to an increase in the calorie content of products. It has been experimentally confirmed that the introduction of hemp flour into bread's minced meat improves the functional and technological indicators of model meat systems. An increase in water-binding capacity was observed, by 13.46‒22.15 %; in water-holding capacity, by 10.34‒21.43 %; in fat-holding capacity, by 17.2‒26.9 %. The combination of semi-fat pork, poultry, mechanically deboned turkey, and hemp flour increases the ductility of the minced meat while reducing the shear stress, contributes to the good forming properties of the minced meat. The sensory analysis of the prototypes showed their high consumer value. The organoleptic assessment and sensory analysis of the prototypes demonstrated high consumer properties of the manufactured products, which makes it possible to recommend them for inclusion in the diets of various segments of the population.
Keywords: hemp flour; physical and chemical properties; pumpkin pulp; meat-containing bread; technological indicators; кафедра технології м’яса і м’ясних продуктів